(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Women’s education in India has a major concern for both government and civil society since educated women can play a very important role in the country’s development. Education is a milestone of empowerment for women because it allows women to respond to challenges, confront their traditional role and change their lives. So we can’t neglect the importance of education in terms of women empowerment and India is poised in recent years to become superpower. Women’s education is the most powerful tool in society for changing position. Women’s education in India was a need of the hour, as education is a foundation stone for women’s empowerment. Education also brings about a reduction in inequalities and functions as a means to improve their status within the family and develops the participation concept. The present attempts to find the relation between educational inequality and empowerment of women. Dividing the entire paper into three parts. The first part is introductory that talks about the second and third goals of MDGs that are achieving universal primary education and promoting gender equality and empowering women to achieve these goals with certain indicators, respectively.